Transformasi Digital dalam Penyelenggaraan Pemerintahan Negeri Batu Merah Kota Ambon - Muhtar Muhtar; Atikah Khairunnisa; Rukoyah Rukoyah (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the digital transformation in the administration of Negeri Batu Merah Government in Ambon City, identify the supporting and inhibiting factors in the implementation of government digitalization, and examine its impact on the quality of public services. The study employed a descriptive qualitative approach with data collection techniques consisting of observation, interviews, and documentation. The research informants included village government officials, administrative staff, and community members as users of public services. The findings indicate that digital transformation in Negeri Batu Merah has been implemented through computer-based administration, digital archiving, and the utilization of digital communication media in public services. The implementation of government digitalization has positively impacted the effectiveness of administrative services, accelerated the dissemination of public information, and improved the efficiency of government officials’ performance. However, the implementation of digital transformation still faces several challenges, including limited information technology infrastructure, low capacity of human resources among government officials, budget constraints, and limited digital literacy within the community. This study concludes that digital transformation plays an important role in creating a more modern, effective, transparent, and responsive local governance system that meets community needs